Shape memory nanocomposite of poly(L-lactic acid)/graphene nanoplatelets triggered by infrared light and thermal heating - S. Lashgari; M. Karrabi; I. Ghasemi; H. Azizi; M. Messori; K. Paderni (eXPRESS Polymer Letters)
In this study, the effect of graphene nanoplatelets (GNPs) on the shape memory properties of poly(L-lactic acid) (PLLA) was studied. In addition to thermal activation, the possibility of infrared actuating of thermo-responsive shape memory PLLA/GNPs nanocomposite was investigated. The incorporated GNPs were expected to absorb infrared wave’s energy and activate shape memory PLLA/GNPs. Different techniques such as differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WAXD), field emission gun scanning electron microscope (FEG-SEM) and dynamic mechanical thermal analysis (DMTA) were used to characterize samples. DSC and WAXD results indicated that GNPs augmented crystallinity due to nucleating effect of graphene particles. GNPs improved both thermal and infrared activating shape memory properties along with faster response. Pure shape memory PLLA was slightly responsive to infrared light and its infrared actuated shape recovery ratio was 86% which increased to more than 95% with loading of GNPs. Drastic improvement in the crystallinity was obtained in nanocomposites with lower GNPs contents (0.5 and 1 wt%) due to finer dispersion of graphene which resulted in more prominent mechanical and shape memory properties enhancement. Infrared activated shape memory PLLA/GNPs nanocomposites can be developed for wireless remote shape control of smart medical and bio-systems.